Selected University of the Philippines Diliman working students' income allocation and contribution to the family income - Siquian, Clarissa Marie T. (UP College of Home Economics, 2011)
The researcher has observed that there is a number of working students in the University of the Philippines Diliman. This may have been caused by the 300% increase in tuition fee last 2007. This observation made the researcher conduct this study to determine the income allocation of the working student; identify regularity and form of the respondents' contribution to the family income; establish the involvement of the respondents in the family decision-making process, particularly in the allocation of the total family income for family expenditures; and to categorize the student's reasons for and benefits into working into: financial, independence, self-improvement and work-experience. The respondents were working students' from the University of the Philippines Diliman, Quezon City, who are pursuing college education at the undergraduate level. They were chosen through purposive sampling. A survey questionnaire was utilized to gather data. Frequencies, percentages and ranking were the methods to analyze the working students' income allocation and family income contribution while content analysis was resorted in categorizing the respondents' reasons/benefits for working. The results showed that working students allocate more for personal expenses than family expenses. they allocated more for food compared to transportation, clothing, savings, school needs, tuition fees, personal care, entertainment and others. The respondents' contribution to the family was in two kinds: cash or kind. They contributed on a monthly or bi-monthly basis. Most of them did not allocate income to family expenditures and they worked to finance their personal needs.